2021
DOI: 10.3389/fneur.2021.730405
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Demographics, and Outcomes of Penetrating Trauma in Sweden During the Past Decade

Abstract: Trauma injury is the sixth leading cause of death worldwide, and interpersonal violence is one of the major contributors in particular regarding injuries to the head and neck. The incidence, demographics, and outcomes of penetrating trauma reaching hospitals in Sweden are not known. We report the largest, nationwide epidemiological study of penetrating injuries in Sweden, using the Swedish Trauma Registry (SweTrau). A multi-center retrospective descriptive study of 4,776 patients was conducted with penetrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
3
18
0
1
Order By: Relevance
“…By crosschecking the prevalence and epidemiology of victims of violent penetrating injuries reported by the SweTrau register and The Swedish National Council for Crime Prevention (BRÅ). The authors of the study found the numbers reported by SweTrau to corresponded well with reports from BRÅ [12].…”
Section: Study Population and The Swetrau Registersupporting
confidence: 78%
“…By crosschecking the prevalence and epidemiology of victims of violent penetrating injuries reported by the SweTrau register and The Swedish National Council for Crime Prevention (BRÅ). The authors of the study found the numbers reported by SweTrau to corresponded well with reports from BRÅ [12].…”
Section: Study Population and The Swetrau Registersupporting
confidence: 78%
“…In our study, these cases most often involved falls and tra c injuries; this was expected, as it is the typical pattern of trauma in Scandinavia [23][24][25]. In Sweden, there are more cases of penetrating trauma injury [57], and RRVs attend such cases about three or four times each week. As Stockholm's ambulance service has not adopted the guidelines for traumatic cardiac arrest, such cases are treated as medical cardiac arrest unless an RRV attends the scene.…”
Section: Discussionsupporting
confidence: 61%
“…Different distributions of penetrating injury have been reported in other countries 10–13. Our results showed that 79% of penetrating injury was caused by stabbing and 0.4% by gunshot.…”
Section: Discussionsupporting
confidence: 47%